Tribology in Engineering - Pihtili, Haşim (IntechOpen, 2013)
The main goal in preparing this book was to publish contemporary concepts, new discoveries and innovative ideas in the field of surface engineering, predominantly for the technical applications, as well as in the field of production engineering and to stress some problems connected with the use of various surface processes in modern manufacturing of different purpose machine parts. This book is an attempt to introduce science into the study of surface treatment processes. Tribology offers a good approach for describing abrasive machining and coating processes and offers the ability to predict some of the outputs of the processes. The study of friction, forces, and energy explores the importance of the various factors which govern the stresses and deformations of abrasion. The effects of grain shape, depth of penetration, and lubrication on the process forces are explored. The tribology of nanostructured surfaces involves many fundamental and scientific issues. More importantly, it has tremendous applications in industries. It is a powerful tool to regulate friction, adhesion, and wetting of surfaces by altering their geometric textures and material compositions at the nanoscale, and, hence, to control the tribological performance of the engineering surfaces.